First record of Gracilaria phuquocensis (Gracilariales, Rhodophyta) in the East Sea of Vietnam - Nguyen, Tu Van; Nguyen, Xuan Vinh; Nguyen, T.H.Tran; Le, Thi Trang; Hoang, Van Duong (Academia Journal of Biology, 2025)
The red algal genus Gracilaria is an important biomaterial for its use in seaweed vegetable and agar industry in Southeast Asia. However, due to the morphological plasticity, the taxonomy and distribution of flattened Gracilaria species remain understudied. Gracilaria phuquocensis N.H.Le, N.Muangmai & G.C.Zuccarello is one of the flattened species described for specimens in the Phu Quoc Islands, Vietnam. Our study aimed to provide morphological details and ecology, and to analyze mitochondrial COI-5P and plastid rbcL sequences of recent collections at My Hoa, Ninh Thuan province. The COI-5P, first generated in G. phuquocensis in the present study, was identical to the sequence from Malaysia. Plastid rbcL sequence divergence of specimens from Malaysia, Philippines, Thailand as well as Vietnam was 0–0.5%, a value similar to intraspecific divergence in Gracilaria species. This result indicates the broad distribution of G. phuquocensis across Southeast Asian waters. Our study provides an intriguing issue for further study on the origin and dispersal of G. phuquocensis in Southeast Asia.